Extracellular synthesis of silver nanoparticles by Thiosphaera pantotropha and evaluation of their antibacterial and cytotoxic effects - Bharti, Sharda (3 Biotech, 2020)
Extracellular biosynthesis of silver nanoparticles (AgNPs) was explored using Thiosphaera pantotropha since this strain exhibits both nitrate- and nitrite-reductase enzyme activity (NaR and NiR, respectively). Optimal AgNP synthesis was achieved using 2 mM AgNO(3), culture supernatant of nutrient broth grown T. pantotropha, and incubation at 37 °C and 180 rpm. Under these conditions, the localized surface plasmon resonance peak of silver at 404 nm matched well with the average size of the spherical AgNPs based on FEG-TEM micrographs, i.e., 14.6 nm (range: 5–51 nm). The zeta potential of −33.6 mV indicated good stability of the biosynthesized nanoparticles. The XRD spectra demonstrated the simultaneous presence of face-centered cubic crystal structure of AgNPs and AgCl NPs. Ag(+) ions were possibly reduced by the NaR and NiR enzymes released into the culture media. The FTIR spectra confirmed the stabilization of the AgNPs by biomolecules present in the culture supernatant of T. pantotropha. The synthesized Ag/AgCl NPs exhibited good antibacterial efficacy against both Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus). The minimum inhibitory concentration (MIC) was 2.5 µg/ml for all the bacteria except B. subtilis (MIC of 10 µg/ml). The minimum bactericidal concentration (MBC) was 2.5, 10, 20, and 5 µg/ml for E. coli, P. aeruginosa, B. subtilis, and S. aureus, respectively. At MBC and higher AgNP concentration, both plating and CLSM imaging confirmed the absence of viable bacteria in treated water. The biogenic AgNPs depicted IC(50) of 34.8 µg/ml for MCF-7 cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-020-02218-0) contains supplementary material, which is available to authorized users.